Development of an enzyme‐linked immunosorbent assay for Bartonella henselae infection detection. (6th June 2014) - Ferrara, F.; Di Niro, R.; D'Angelo, S.; Busetti, M.; Marzari, R.; Not, T.; Sblattero, D.
Abstract Several serological diagnostics rely on enzyme‐linked immunosorbent assay (ELISA) to detect bacterial infections. However, for some pathogens, including Bartonella henselae, diagnosis still depends on manually intensive, time‐consuming assays including micro‐immunofluorescence, Western blotting or indirect immunofluorescence. For such pathogens, there is obviously still a need to identify antigens to establish a reliable, fast and high‐throughput assay (Dupon et al. 1996). We evaluated two B. henselae proteins to develop a novel serological ELISA: a well‐known antigen, the 17‐kDa protein, and GroEL, identified during this study by a proteomic approach. When serum IgG were tested, the specificity and sensitivity were 76 and 65·7% for 17‐kDa, respectively, and 82 and 42·9% for GroEL, respectively. IgM were found to be more sensitive and specific for both proteins: 17‐kDa protein, specificity 86·2% and sensitivity 75%; GroEL, specificity 97·7% and sensitivity 45·3%. IgM antibodies were also measured in lymphoma patients and patients with Mycobacterium tuberculosis infection to assess the usefulness of our ELISA to distinguish them from B. henselae infected patients. The resulting specificities were 89·1 and 93·5% for 17‐kDa protein and GroEL, respectively. Combining the results from the two tests, we obtained a sensitivity of 82·8% and a specificity of 83·9%. Our work described and validated a proteomic approach suitable to identify immunogenic proteins useful for developing a serological test of B. henselae infection. Significance and Impact of the Study A reliable serological assay for the diagnosis of Cat Scratch Disease (CSD) – a pathological condition caused by Bartonella henselae infection – has not yet been developed. Such an assay would be extremely useful to discriminate between CSD and other pathologies with similar symptoms but different aetiologies, for example lymphoma or tuberculosis. We investigate the use of two B. henselae proteins – GroEL and 17‐kDa – to develop a serological‐based ELISA, showing promising results with the potential for further development as an effective tool for the differential diagnosing of B. henselae infection.